Cykle rozwojowe a wahania produkcji rolniczej w Polsce w latach 1950 - 1984 (próba history czno-ekonomicznej analizy przyczyn) - Ławniczak, Irena (Wydział Prawa i Administracji UAM, 1986)
The article is an attempt at finding causes of cyclical fluctuations of agricultural policies in Poland in the years 1950 -1984, with the use of the quantitative method. The economic and historical analysis of the productional effects achieved in agriculture in Poland throughout the examined period allows to present the hypothetical statement that: 1. Development cycles present in the postwar Poland and consisting of the phase „A" and „B" are the result of a higher or lower dynamics of growth. 2. Phase „A" of each cycle is characterized by the higher rate of investment growth in the branch of means of production, phase „B" produces the lower rate, while the investment rate is higher in the branch of consumption goods and agriculture. 3. Changes of the rate and directions of investments result in a decrease or increase of agricultural production measured by the value of final production per 1 ha of arable land. The changes are effected in relation to the changes in the rate of agricultural investments and the rate of their growth with a one-phase lag.
Development Cycles and Agricultural Production Fluctuations in Poland in the Years 1950 - 1984 (an Attempt at Historical and Economical Analysis of the Causes)